Potentials of Edible Canna (Canna edulis Kerr) Starch for Bioplastic: A Review - Gabriel, Azmi Alvian; Solikhah, Anggita Fitri; Rahmawati, Alifia Yuanika; Taradipa, Yunita Sasmi; Maulida, Erni Tsania (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractStarch-based bioplastic was more economical and competitive compared to bacteria-based bioplastics (polylactic acid, polybutylene succinate, and polyhydroxyalkanoates) due to the starch variances and the availability in Indonesia, along with the simple techniques that can be applied. This review aimed to describe the potential and opportunities of edible canna starch as an alternative raw material of bioplastics production. Edible canna tuber productivity in Java, Indonesia, with a harvest age of about eight months reaches 30-49.4 tons/ha. It will produce a mature segment 70.2% of the total harvest weight. Edible canna tuber was a carbohydrate source that contains 88.10% starch with an advantage of 68% higher fiber and mineral content than other tubers. Furthermore, canna tuber starch contains amylose proportions of 35.0%. The high amylose content in canna starch is one of the properties that can position its function for developing packaging materials. The gelatinization process of canna starch requires a short time and low energy because of its large granule size (56 μm). A literature review of canna starch as an alternative of bioplastic raw materials needs to be carried out to obtain accurate data and information regarding treatment, use of additional materials, and characteristics of bioplastic products resulting from experimental studies so that they can be further implemented.Keywords: bioplastics, edible canna, starch AbstrakPenggunaan pati sebagai salah satu bahan utama produksi bioplastik bernilai lebih ekonomis dan kompetitif dibandingkan dengan bioplastik berbasis bakteri (polylactic acid, polybutylene succinate, dan polyhydroxyalkanoates) karena variasi dan jumlahnya yang melimpah di Indonesia dan teknologi sederhana yang dapat diaplikasikan. Tujuan kajian literatur ini adalah untuk menggambarkan potensi dan peluang pati ganyong sebagai alternatif bahan baku pembuatan bioplastik. Produktivitas umbi ganyong di Pulau Jawa dengan umur panen sekitar 8 bulan mencapai 30-49,4 ton/ha. Ganyong merupakan sumber karbohidrat yang mengandung 88,10% pati dengan keunggulan berupa 68% kandungan serat dan mineral pada pati yang lebih tinggi dibanding umbi-umbian lain. Pati umbi ganyong juga mengandung amilosa sebanyak 35,0%. Kandungan amilosa yang tinggi pada pati ganyong merupakan salah satu sifat yang berfungsi dalam pengembangan bahan pengemas. Proses gelatinisasi pati ganyong membutuhkan waktu yang sebentar dan energi yang rendah karena ukuran granulnya yang besar (56 m). Kajian pustaka pati ganyong sebagai alternatif bahan baku bioplastik perlu dilakukan untuk mendapatkan keakuratan data dan informasi mengenai perlakuan, penggunaan bahan tambahan, dan karakteristik produk bioplastik yang dihasilkan dari kajian eksperimen agar dapat diimplementasikan lebih lanjut.Kata kunci: bioplastik, ganyong, pati